Principles and practice of pediatric infectious diseases - Long, Sarah S.; Pickening, Larry K.; Prober, Charles G. (Elsevier, 2012)
Provides comprehensive coverage you need to understand, diagnose, and manage the ever-changing, high-risk clinical problems caused by pediatric infectious diseases.